2020
DOI: 10.15537/smj.2020.12.05582
|View full text |Cite
|
Sign up to set email alerts
|

Natural immunity to influenza A and B among Saudi blood donors in Al Madinah Al Munawarah, Saudi Arabia

Abstract: Objectives: To investigate the seroprevalence of influenza viruses (A and B) among blood donors in Kingdom of Saudi Arabia. Methods: The present investigation was conducted between April 2019 and July 2019. Participants were healthy adults recruited from the central blood bank Al Madinah Al Munawarah, Kingdom of Saudi Arabia. Immunoglobulin G (IgG) levels against influenza A and B were measured in serum samples using ELISA. Original Article Results: The results showed that 29.2% of the sample had significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Interestingly, a significant correlation between age and influenza B antibody levels but not with influenza A was found in our study, unlike Mahallawi et al study in which they observed the significance with influenza A but not B. 12 We found that for influenza A, the antibody level was highest compared to influenza B. Fourteen participants (5.5%) presented the highest antibody level the test can detect. Samples' dilution was according to the manufacturer's instructions in which 5 μl of the serum sample were added in 100 μl serum diluent, and no further dilutions done to all samples.…”
Section: Influenza a Igg And B Igg Antibodies Versus Age And Vaccinat...contrasting
confidence: 90%
“…Interestingly, a significant correlation between age and influenza B antibody levels but not with influenza A was found in our study, unlike Mahallawi et al study in which they observed the significance with influenza A but not B. 12 We found that for influenza A, the antibody level was highest compared to influenza B. Fourteen participants (5.5%) presented the highest antibody level the test can detect. Samples' dilution was according to the manufacturer's instructions in which 5 μl of the serum sample were added in 100 μl serum diluent, and no further dilutions done to all samples.…”
Section: Influenza a Igg And B Igg Antibodies Versus Age And Vaccinat...contrasting
confidence: 90%
“…Influenza is a contagious disease caused by influenza viruses that infect the nose, throat, and sometimes the lungs. The virus infects host epithelia cells by binding of surface glycoprotein haemagglutinin (HA) to sialic acid receptor on the cell surface ( Barbey-Martin et al, 2002 , Mahallawi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Saudi Arabia noted that seroprevalence of antibodies against influenza A viruses was 29.2%. 13 Seroprevalence of antibodies against H1N1 was 30% in Mali. 14 A study in Nigeria estimated that 56.6% of pregnant women had antibodies against influenza A viruses.…”
Section: Discussionmentioning
confidence: 98%
“…The positivity titers 1:160 and 1:320 had the highest percentage at Follow up 2 for both H3N2 and H1N1. A study in Saudi Arabia noted that seroprevalence of antibodies against influenza A viruses was 29.2% 13 . Seroprevalence of antibodies against H1N1 was 30% in Mali 14 .…”
Section: Discussionmentioning
confidence: 99%